Thyroglossal duct cyst carcinoma - Biswas, Ashim Kumar; Salam, Kazi Shameemus; Uddin, Md. Mosleb; Saha, Kanu Lal; Siddiquee, Belayat Hossain; Islam, Mohammad Asraful (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Thyroglossal duct cyst carcinoma in a rare condition. Only around 250 cases of malignant thyroglossal cyst have been reported as far. We report a 45 years old women presenting with a painless swelling in the midline in the upper part of front of neck for 1 yr. This swelling moves with deglutition, multilobulated moves up on protrusion of tongue. FNAC revealed cystic lesion compatible with thyroglossal duct cyst. Ultrasonogram revealed mass is separated from thyroid gland. Patient underwent sistnmk's operation and tissue was sent for histopathological examination and report reveled papillary carcinoma of thyroglossal duct cyst.